Social robotics as an educational tool for students with ASD: Case Study - Corrales Castaño, Laura; Rodríguez Torres, Javier (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The incorporation of the students with autism spectrum disorder in the ordinary schools has meant an advance in the educational inclusion. We intend to analyze the possibilities that social robotics may provide in educational interventions with these students. The method used is the case study in which we try to give a qualitative description of a very particular situation in a very diverse and heterogeneous reality. The incorporation of the social robot in the educational process of an ASD student, has developed the interaction in a gaming context just as the acquisition of contents.